MODELING AND ANALYSIS OF CHEMICAL REACTIONS IN CATALYTIC PELLETS WITH NON-UNIFORM CATALYST DISTRIBUTION - Marx, Zhanar (Nazarbayev University Graduate School of Engineering and Digital Sciences, 2024)
This thesis explores the modeling and analysis of chemical reactions in catalytic pellets with non-uniform catalyst distribution, focusing mainly on core-shell structures with an inert shell. Recognizing the critical role of heterogeneous catalysis in various industrial processes, this study delves into how the spatial distribution of the active catalytic material within the pellets influences reaction efficiency and catalyst performance. Utilizing a combination of analytical and numerical methods, this research addresses the distribution of active material following a Gaussian profile within a spherical and slab-type pellet, a scenario less explored in existing literature. The study conducted modeling of core-shell catalytic pellets with an inert shell, examining two particle shapes: sphere and slab. Analytical solutions for the intra-particle reactant concentration were obtained by solving reaction-diffusion equations for an isothermal irreversible first-order reaction. Then, the mass balance equations were solved numerically and compared with the corresponding analytical solutions. Consequently, the mathematical model and its numerical solution were developed to include a Gaussian distribution of catalytic material in the active layer, and the equations are derived to account for non-isothermal reactions with arbitrary kinetics. The findings highlight the impact of the distribution of active material on the catalytic reaction rates, demonstrating that non-uniform distribution, particularly the Gaussian profile, can enhance catalyst performance compared to uniform distribution. Additionally, the parametric analysis on the effect of process and reaction parameters on catalyst effectiveness factor is carried out.
Keywords: type of access: open access; heterogeneous catalysis; core-shell pellets; Gaussian activity distribution; power-law kinetics; numerical analysis; parametric study.